2022
DOI: 10.1371/journal.pone.0260998
|View full text |Cite
|
Sign up to set email alerts
|

Transection injury differentially alters the proteome of the human sural nerve

Abstract: Regeneration after severe peripheral nerve injury is often poor. Knowledge of human nerve regeneration and the growth microenvironment is greatly lacking. We aimed to identify the regenerative proteins in human peripheral nerve by comparing the proteome before and after a transection injury. In a unique study design, we collected closely matched samples of naïve and injured sural nerve. Naïve and injured (two weeks after injury) samples were analyzed using mass spectrometry and immunoassays. We found significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Besides, SCs transdifferentiated or reprogrammed from a mature form into a repair phenotype. Chau et al (2022) reached a similar conclusion in a study of transection injury to the human sural nerve.…”
Section: Mechanism Of Scs Promoting Peripheral Nerve Repairsupporting
confidence: 53%
“…Besides, SCs transdifferentiated or reprogrammed from a mature form into a repair phenotype. Chau et al (2022) reached a similar conclusion in a study of transection injury to the human sural nerve.…”
Section: Mechanism Of Scs Promoting Peripheral Nerve Repairsupporting
confidence: 53%
“…TMT proteomics and data analyses were performed as previously described [ 46 , 47 ]. Proteins from flash‐frozen cell pellets (1e6 cells per pellet, n = 3 per cell line) were reduced, alkylated, and purified by chloroform/methanol extraction prior to digestion with sequencing grade modified porcine trypsin (Promega, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies of the early and late responses of Schwann cells and other central players in the nerve degeneration and regeneration processes have focused on the events in animals. Few studies have studied the protein response in injured human peripheral nerves [133][134][135] or in humans with type 1 and type 2 diabetes [85,136]. It has been reported that two major genes, associated with repair Schwann cells, c-Jun and p75 NTR , are up-regulated in injured human nerves in healthy subjects, while the myelin-associated transcription factor (EGR2) is down-regulated [135].…”
Section: Genes and Proteomics In Human And Animal Nerves After Injury...mentioning
confidence: 99%
“…It has been reported that two major genes, associated with repair Schwann cells, c-Jun and p75 NTR , are up-regulated in injured human nerves in healthy subjects, while the myelin-associated transcription factor (EGR2) is down-regulated [135]. In a proteomics study of the sural nerve that was subjected to a nerve injury (surgery in patients with idiopathic Parkinson's disease in connection with nerve grafting into substantia nigra; control nerve and then distal nerve end harvested at two weeks follow up; age 50-70 years), 8/20 most prominently up-regulated pathways were associated with gene expression through translation, while the top down-regulated pathways were associated with cytoskeletal organization or structure as well as to neuron and synapses [133]. Detailed changes were reported concerning growth factors (e.g., glial cell-derived neurotrophic factor; GDNF, brain-derived neurotrophic factor; BDNF; transforming growth factor-β; TGF-β and VEGF), myelination, Schwann cell differentiation (e.g., c-Jun), regulation of apoptotic processes, and response to "axonal injury" [133,137].…”
Section: Genes and Proteomics In Human And Animal Nerves After Injury...mentioning
confidence: 99%
See 1 more Smart Citation